Influence of Thyroid Mass and Shape on the Internal Dosimetry of 131 I - Lai Zhou; Yuanyuan Liu; Bin Wu; Xiangpeng Meng; Yu Wang; Ao Ju; Jiali Qian; Sirun Gong; Xinxin Chen; Congchong Yan; Jianping Cheng (Health Physics, 2026)
Radionuclide 131 I is of vital importance in radiation protection and nuclear medicine. Its internal dose is mainly concentrated in the thyroid. The S value is a key parameter in the calculation of internal dose. It represents the radiation-weighted energy deposition per unit mass of the target organ when the radionuclide undergoes a single decay of the source organ. As the thyroid is both the source organ and the target organ, its mass and shape may affect the S value. Therefore, this paper studies the influence of thyroid mass and shape on the S value. In this study, based on the thyroid model of the ICRP adult mesh-type reference computational phantoms (MRCPs), a series of thyroids with different masses were generated by proportionally scaling the thyroid volume while maintaining its original shape. The influence of mass on the S value (thyroid←thyroid) is then systematically analyzed using the Geant4 Monte Carlo simulation platform. To further explore the influence of shape, this paper reviews the S values (thyroid←thyroid) simulated by other researchers using thyroid models of different shapes and compares them with the research results of this paper. The research results show that the S value has a good inversely proportional relationship with thyroid mass. It can be precisely fitted as a linear function of the reciprocal of mass, with a correlation coefficient (R 2 ) of 0.9999. The result of this formula has a deviation of within 5.67% compared with the results in the literature. This study demonstrates that the difference in thyroid shape has a relatively weak influence on the S value, and the empirical formula fitted in this paper may have good universality and reliability.